2011
DOI: 10.1097/phm.0b013e3181f703ef
|View full text |Cite
|
Sign up to set email alerts
|

Frail Institutionalized Older Persons

Abstract: The objective of this study was to perform a systematic review on training outcomes influencing physical fitness, activity of daily living performance, and quality-of-life in institutionalized older people. We reviewed 27 studies on older people (age, ≥70 yrs) in long-term care facilities and nursing homes. Our ultimate goal was to propose criteria for an evidence-based exercise protocol aimed at improving physical fitness, activity of daily living performance, and quality-of-life of frail institutionalized ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(56 citation statements)
references
References 37 publications
4
51
0
1
Order By: Relevance
“…Based on a Cochrane review, there is a strong evidence to indicate that exercise targeting endurance, flexibility, balance and strength in community-dwelling frail elders can prevent disability [205]. Similar findings were demonstrated in a systematic review of exercise training programs (n = 27 studies; n = 6459 patients) in frail elders living in LTC facilities [206]. Multiple studies have shown that resistance training in healthy and frail adults can increase physical strength, improve gait speed, reduce the risk of falls or delay the onset and progression of frailty [207][208][209][210].…”
Section: Patient-level Management Identify and Minimize Risk Factors Thsupporting
confidence: 57%
“…Based on a Cochrane review, there is a strong evidence to indicate that exercise targeting endurance, flexibility, balance and strength in community-dwelling frail elders can prevent disability [205]. Similar findings were demonstrated in a systematic review of exercise training programs (n = 27 studies; n = 6459 patients) in frail elders living in LTC facilities [206]. Multiple studies have shown that resistance training in healthy and frail adults can increase physical strength, improve gait speed, reduce the risk of falls or delay the onset and progression of frailty [207][208][209][210].…”
Section: Patient-level Management Identify and Minimize Risk Factors Thsupporting
confidence: 57%
“…However, they failed to show any effects on functional performance assessed as grip strength, walking ability, stair climbing and mobility. In contrast, in three systematic reviews [1,11,12] evidence was found showing that physical training had positive effects on mobility, physical functioning and cognition in institutionalized older patients. A Cochrane study [1] concluded that physical rehabilitation in long-term care residents is worthwhile and safe, that it reduces disability and leads to few adverse events such as pain, chest pain or loss of balance.…”
Section: Introductionmentioning
confidence: 96%
“…As for institutionalized older persons and frail older persons, there is evidence for training effects on physical fitness, functional performance, and performance of activities of daily living 14,16…”
Section: Introductionmentioning
confidence: 99%